PERANCANGAN INTERIOR HONEY SPA DI SURAKARTA - sela Merigrin Setyowati; Siti Badriyah (Fakultas Seni Rupa dan Desain, Institut Seni Indonesia Surakarta, 2020)
ABSTRACT The city of Surakarta has cultural and economic potential that has been known to come out of the region, especially in the fields of tourism, business and trade, so that the opportunity for the establishment of infrastructure in the field of skin care has the opportunity. The design of the Honey Spa Interior in Surakarta is an alternative honey-based beauty and body treatment facility with a smooty and shinny theme, which has a contemporary-style interior. The design of the Honey Spa Interior in Surakarta uses a practical function approach, ergonomics and themes. The design method refers to the design process.Keywords: Interior Designing, Honey Spa, Contemporary Style, SurakartaABSTRAK Kota Surakarta memiliki potensi budaya dan ekonomi yang telah dikenal sampai keluar daerah terutama di bidang pariwisata, bisnis dan perdagangan sehingga berpeluang untuk berdirinya infrastruktur di bidang perawatan kulit. Perancangan Interior Honey Spa di Surakarta ini adalah suatu alternatif sarana perawatan kecantikan dan tubuh berbahan dasar madu dengan tema smooty and shinny yang interiornya bergaya Kontemporer. Perancangan Interior Honey Spa di Surakarta menggunakan pendekatan fungsi praktis, ergonomi, dan tema. Metode desain mengacu pada proses desain.Kata kunci: Perancangan Interior , Honey Spa, Gaya Kontemporer, Surakarta